The impact of natural dust aerosol on warm and cold cloud formation - Koehler, Kirsten, author; Kreidenweis, Sonia M., advisor (Colorado State University. Libraries, 2008)
Dust particles' ability to scatter and absorb radiation and their potential to interact with water vapor may lead to important direct and indirect radiative impacts on the climate. Due to differences in solubility, hygroscopicity, chemical and surface properties, dust particles from different regions may interact with cloud development in a variety of ways that are not fully understood. In this work four types of dust from the Southwestern U.S. and Northern Africa were studied. The characteristics of the samples used cover a range of soluble contents, geographic locations of origin, and collection methods. Hygroscopic growth of the particles was determined using a humidified tandem differential mobility analyzer (HTDMA) at relative humidities (RH) from 5-95% and cloud condensation nuclei (CCN) activity was measured using a continuous flow CCN counter at supersaturations up to 2%. At cold temperatures (-60<T<-20°C), the ice nucleation behavior was examined using the Colorado State University continuous flow diffusion chamber (CFDC) for RH values from ice saturation to significantly above water saturation. The data suggest that atmospheric dust particles have potential effects on both warm and cold cloud formation. Even the limited CCN activity determined for some samples could be relevant to cloud drop formation in the atmosphere, because dust aerosols generally have relatively large number concentrations of particles with diameters larger than 400 nm. Thus, the potential for dust particles to serve as large and giant CCN must be considered in determining the role of dust in warm cloud formation. Many dust samples showed the ability to heterogeneously nucleate ice at low RH. The particles which initiated the ice phase at the lowest RH conditions appear to be those with the smallest contents of soluble material. This interpretation of the data was substantiated by coating the most IN active dust sample with secondary organic compounds, which resulted in an increase in RH required for ice phase initiation. Therefore, the impact of the dust on cold cloud formation may depend on the way freshly emitted dust ages in the atmosphere.
Keywords: aerosol indirect effects; CCN activity; cloud condensation nuclei; hygroscopicity; ice nucleation; mineral dust; atmospheric sciences